Submuscular bridge plating of length-unstable paediatric femoral shaft fractures in children between the ages of 6 and 13 - Salkinder, Rael; Du Toit, J.; Lamberts, R. P. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed (Orth))--Stellenbosch University, 2014.